How Do Gender Norms Shape Education and Domestic Work Outcomes? The Case of Syrian Refugee Adolescents in Jordan - Krafft, Caroline; Ragui, Assaad; Pastoor, Isabel (World Bank, Washington, DC, 2021)
Forced displacement has disrupted Syrian refugees’ lives and exposed them to new communities and norms. This paper assesses how gender norms shape the lives of Syrian refugee adolescent girls in Jordan, using nationally representative data. Factor analysis is used to summarize a variety of beliefs and behavioral aspects of norms: gender role attitudes, justification of domestic violence, decision making, and mobility. The paper compares these outcomes by sex, nationality, and for adolescents versus adults. It complements the data on individual beliefs and behaviors with family and community beliefs and behaviors as proxies for others’ expectations and behaviors. The paper then examines how own, family, and community gender norms relate to two key adolescent outcomes: domestic work and enrollment in school. The findings show that while gender role attitudes are similar across generations and nationalities, Syrian adolescent girls are particularly restricted in their mobility. Nonetheless, they have similar educational outcomes as boys and, after accounting for differences in socioeconomic status, as Jordanian girls. While gender inequality in domestic work is substantial, higher levels of own and mother’s decision making predict lower domestic workloads, illustrating the linkages between different dimensions of gender norms and social and economic outcomes.